2012
DOI: 10.1002/elan.201200373
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Activation of the Natural Catalytic Cycle of Cytochrome P450s in Human Liver Microsomes

Abstract: The natural catalytic cycle of cytochrome (cyt) P450 enzymes in human liver microsome (HLM) films was activated electrochemically via the electron transfer sequence electrode→cyt P450 reductase (CPR)→cyt P450. Cyclic voltammograms for HLM films had midpoint potentials of −0.50 V vs. SCE at pH 7.4 characteristic of CPR, not cyt P450s. HLM and CPR microsomes without cyt P450s did not electrocatalytically reduce H2O2, and did not shift midpoint potential when CO was added, also indicating that the peaks do not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Cyt P450 inhibition 34,45,46 can result in situations in which one drug (or another molecule) inhibits a cyt P450 isoform that metabolizes a second drug. Co-administration of two such drugs can result in high plasma concentrations of the more slowly metabolized drug that can cause toxic effects known as drug–drug interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyt P450 inhibition 34,45,46 can result in situations in which one drug (or another molecule) inhibits a cyt P450 isoform that metabolizes a second drug. Co-administration of two such drugs can result in high plasma concentrations of the more slowly metabolized drug that can cause toxic effects known as drug–drug interactions.…”
Section: Resultsmentioning
confidence: 99%
“…15,3234 Following the enzyme reactions, washing with anaerobic 50 mM phosphate buffer + 0.1 M NaCl of pH 7.4 was done for 3 min at 500 µL min −1 . Then, 1.25 V vs. Ag/AgCl was applied to the array for 180 s with a CHI 1232 electrochemical analyzer (CH Instruments Inc.) to generate ECL acquisition which is detected by the CCD camera.…”
Section: Methodsmentioning
confidence: 99%
“…33 This suggests that the observed voltammetric properties of microsomal films are characteristics of oxidoreductases in microsomes. [13][14][15] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 The peak currents increased linearly with scan rates from 0.005 to 2 Vs -1 for the immobilized microsomal films on all four carbon electrodes ( Figure S4). This property confirms the surface-confined redox voltammetry of HLM.…”
Section: Electrochemical Probing Of Microsomal Film Voltammetrymentioning
confidence: 99%
“…Cyclic voltammetry (CV) of this system revealed that it closely mimics the details of the natural cyt P450 catalytic pathway . We also found that a similar pathway can be accessed in microsomes containing multiple cyt P450s and CPR . We showed by CV that electrons in these systems flow from the electrode to CPR and then to the cyt P450, the same as in the in vivo pathway.…”
Section: Electrochemical Toxicity Biosensorsmentioning
confidence: 59%
“…We exploredw ays to place proteins in film environments that facilitate electron exchange with underlying electrodes for electrode-driven cyt P450 biocatalysis [28] including( 1) adsorbed DNAf ilms that bind cyt P450s, ( 2) cyt P450s in multilayered films of insoluble lipids [29][30]; and (3) LbL films of cyt P450s made with polyion films that can also contain DNA. Gilardi and coworkers developed fusion proteins in which an initial electrona cceptor protein is linked to ac yt P450 to activate the cyt P450 Fe III .I nt hese systems,e lectrons flow from the electrode, to the initial electrona cceptor and then to the cyt P450 [32].C atalytic activity in these fusion proteinsc an be optimizedb yc ontrolling the electron transferr ate due to longer lived cytP 450 iron-peroxy species [ 33].O ur most successful approach for an atural catalysis pathway employed microsomal CPR/cyt P450 films on electrodes with al arge excess of cytP 450 over CPR, similar to the situation in vivo.C yclic voltammetry (CV) of this system revealed that it closely mimics the details of the natural cyt P450 catalytic pathway [34].W ealso foundthat asimilar pathway can be accessedi nm icrosomes containing multiple cyt P450s and CPR [35].W es howed by CV that electrons in these systems flow from the electrode to CPR and then to the cyt P450, the same as in the in vivo pathway.S pectroscopic studies of CO binding showed that cyt P450s are in the native form in these films.T he model best fittingt he data includesa ne quilibriumr edox reactioni nvolving aC PR-cyt P450 complex that facilitates efficient catalytic turnover of the excess cyt P450s. Microsomal CPR/cytP 450 films gave midpoint potentials near À490 mV vs.S CE (À250 mV vs.N HE) ( Figure 1A).…”
Section: Cyt P450 Catalysis On Electrodesmentioning
confidence: 99%